The Mugshot Industry: Freedom of Speech, Rights of Publicity, and the Controversy Sparked by an Unusual New Type of Business - Allen Rostron (Washington University Law Review, 2013)
Matthew Creed, a young entrepreneur in suburban Kansas City, decided to start a business. He created a website called BlabberMouth featuring the names, addresses, and mugshot photographs of local people recently arrested. He then mailed letters to the arrestees, informing them about the website and offering to delete the information upon payment of a 199.99 fee. “We have already started blabbing to the world about your release from jail,” the letter declared, “[a]nd we want to make you aware of our services, as we kind of have a big mouth.” The letters added that those who failed to pay the fee might see their neighborhoods flooded with fliers further publicizing the arrests. “We will canvas the neighborhood of someone just released from jail with flyers on every residence,” the letter warned, “even if they have not gone to trial or been convicted of the crimes brought against them.” The public outcry against Creed’s business venture was intense. Local law enforcement promised to investigate whether it violated any laws. Creed received death threats. People angry about BlabberMouth’s business tactics soon discovered that Creed had once been arrested for drunk driving and that several of his relatives also had arrest records; they began posting mugshots and information about those arrests on the Internet. Just a week after the first news reports about his business appeared, Creed apologized and announced that he had decided to shut down the BlabberMouth business. While BlabberMouth was a short-lived enterprise, the mugshot industry remains alive and well, with many companies around the nation profiting from the dissemination of mugshot photos. This new type of business arouses strong feelings on both sides, with critics charging that it amounts to a form of blackmail, while the mugshot companies contend that they provide a beneficial public service protected by freedom of speech. The mugshot industry raises intriguing legal questions, and yet these issues have received remarkably little attention from courts or legal scholars to date. Indeed, the controversy surrounding the mugshot industry’s practices has yet to be the subject of any court decisions or analysis in law journals. In this article, I begin the process of exploring the difficult questions surrounding mugshot businesses. In my view, people targeted by businesses like BlabberMouth have a viable theory under which to seek legal relief, but a line must be carefully drawn between businesses that merely profit by reproducing mugshot photos and those that take the further step of agreeing not to publicize a mugshot or other arrest information in exchange for payment of a fee.
Keywords: BlabberMouth; Matthew Creed; mugshot; blackmail; arrest